PERLINDUNGAN HUKUM TERHADAP PENGUNGSI (REFUGEE) ROHINGYA YANG BERADA DI INDONESIA SEBAGAI NEGARA YANG BELUM MERATIFIKASI KONVENSI TENTANG PENGUNGSI 1951 DAN PROTOKOL TAMBAHAN 1967 - Mhd Irpan Pulungan; Evi Deliana; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
People who make the move or commonly called refugees can be in the form individual or groups. Refugees not only come from one region to another in the same country, however its not uncommon for refugees to move from one country to another in order to seek protection for their human rights both for themselves and relatives and family (groups). Indonesia is a country that has been affected by a wave of refugees in recent years. Indonesia is made a transit country to go third countries as a destination for refugees, because Indonesia is the most ideal place for refugee stops. The problem of refugees now is the influx of refugees from Myanmar, and one of the countries affected by the Rohingya ethnic displacement is Indonesia. Writing this thesis, namely: First, to find out the legal protection of Rohingya refugees who are in Indonesia. Second, to know the attitude and policy of Indonesia in dealing with Rohingya refugees in Indonesia as a recipient country that has not ratified the 1951 Refugee Convention and the 1967 Additional Protocol.This type of research can be classified, normative legal research type. because in this study describes clearly and in detail about the legal protection of Rohingya refugees in Indonesia. Data sources used are secondary data sources consisting of primary data, secondary data, and tertiary data, data collection techniques, namely library research, then the data collected is analyzed to draw conclusions.From the results of the research and discussion it can be concluded that, Firstly although Indonesia is one of the countries that has not ratified the rules regarding the 1951 Convention on Refugees and Additional Protocols in 1967, Indonesia as a country still provides protection. Where the Indonesian government gives authority to UNHCR and IOM to deal with the problem of refugees who are in Indonesia. One form of protection is to provide costs and meet the needs of refugees while in Indonesia. Second, Indonesia has set its attitude and policy in dealing with Rohingya refugees as recipient countries that have not ratified it by establishing the principle of non-refoulement. The principle of non-refoulement is the principle listed in article 33 of the 1951 Convention which contains a prohibition on the eviction and return of refugees. 125 of 2016.Keywords: Legal Protection, Rohingya Refugees, The 1951 Convention and The 1967 Protocol